1974
DOI: 10.1042/bj1410675
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and thiol reactivity of human plasma clotting factor XIII

Abstract: 1. The reaction of iodoacetate, 2-chloromercuri-4-nitrophenol and 5,5'-dithiobis-(2-nitrobenzoate) with thrombin-cleaved Factor XIII (i.e. Factor XIII(a)) was accompanied by enzyme inhibition. 2. The reaction with iodoacetate and 5,5'-dithiobis-(2-nitrobenzoate) was absolutely dependent on Ca(2+), and the rate of reaction increased with the Ca(2+) concentration up to very high, non-physiological concentrations. 3. 2-Chloromercuri-4-nitrophenol reacted with Factor XIII(a) in the absence of Ca(2+), but at a much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Calcium appears to play an intriguing regulatory role in FXIII [1920, 5051]. Low mM levels already begin to initiate important conformational changes needed to expose the active site and make the enzyme ready to accommodate incoming substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium appears to play an intriguing regulatory role in FXIII [1920, 5051]. Low mM levels already begin to initiate important conformational changes needed to expose the active site and make the enzyme ready to accommodate incoming substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chelating CaZ+ with ethelenediaminetetraacetic acid disodium salt (EDTA) or ATP, or inactivating the enzyme by Zn2+ [ 161 , mercurials, or disulfides [17] , the above type of formulation of the pathway suggests that primary aminesif they satisfy the specificity requirements of the enzymemight interfere with the formation of the P-CONH-P' product. Indeed, we found that such synthetic compounds could inhibit cross-linking rather effectively even in the complex biological system of clotting in whole blood [13, 181.…”
Section: Transamidase-catalyzed Cross-linking Of Proteinsmentioning
confidence: 99%
“…Ca2+ causes Factor XIIIa to dissociate into sub-units, the a' subunits subsequently aggregating into a misty precipitate (Cooke & Holbrook, 1974b), and is also required for inhibition of the essential thiol of plasma Factor XIII (Cooke et al, 1974). The Ca2+ concentrations required for both these processes are very much higher than that required to observe maximum assay rates, indicating that they may be non-physiological reactions.…”
mentioning
confidence: 99%